Clinical signs, therapy and zoonotic risk of pet guinea pigs with dermatophytosis. Issue 2 (31st July 2012) - Kraemer, A.; Hein, J.; Heusinger, A.; Mueller, R. S.
Summary Systematic studies about pet guinea pigs with dermatophytosis are rare. The aim of this study was to evaluate clinical signs, therapy and zoonotic risk of pet guinea pigs with dermatophytosis. Questionnaires from both owners (n = 74) of pet guinea pigs with dermatophytosis and their veterinarians (n = 101) were analysed regarding clinical signs, therapy and data pertinent to zoonotic potential. Trichophyton (T.) mentagrophytes was found in 97% of cases. In the weeks preceding the onset of the clinical signs, a new guinea pig joined the household in 43% of cases. One third of the affected guinea pigs had lived in the household for less than 3 months. Predominant clinical signs were alopecia (83%), scaling (73%) and crusting (70%). The most commonly affected body site was the head (75%). In approximately one quarter of the cases humans showed clinical signs of dermatophytosis, in half the households, only children were affected. Skin lesions were seen most often on the face, the neck and the arms. Pet guinea pigs carrying dermatophytes must be considered a serious zoonotic risk for their owners, especially for children. A major risk factor for dermatophytosis seems to be a recent acquisition of a new guinea pig.